2017
DOI: 10.1371/journal.pone.0170437
|View full text |Cite
|
Sign up to set email alerts
|

The salivary microbiome is altered in the presence of a high salivary glucose concentration

Abstract: BackgroundType II diabetes (T2D) has been associated with changes in oral bacterial diversity and frequency. It is not known whether these changes are part of the etiology of T2D, or one of its effects.MethodsWe measured the glucose concentration, bacterial counts, and relative frequencies of 42 bacterial species in whole saliva samples from 8,173 Kuwaiti adolescents (mean age 10.00 ± 0.67 years) using DNA probe analysis. In addition, clinical data related to obesity, dental caries, and gingivitis were collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
77
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(87 citation statements)
references
References 49 publications
4
77
0
6
Order By: Relevance
“…In our late food timing condition, we found higher microbial diversity during the middle of the day, as compared with the early food timing condition in salivary microbiota. This finding suggests that eating late would drive changes in salivary microbial diversity in a similar direction to that observed in obesity and inflammation (54).…”
Section: Discussionmentioning
confidence: 56%
“…In our late food timing condition, we found higher microbial diversity during the middle of the day, as compared with the early food timing condition in salivary microbiota. This finding suggests that eating late would drive changes in salivary microbial diversity in a similar direction to that observed in obesity and inflammation (54).…”
Section: Discussionmentioning
confidence: 56%
“…Goodson et al. studied a large population of adolescents and demonstrated an overall reduction in total salivary bacterial load and in the bacterial counts of almost every species tested with increasing salivary glucose concentration . Also, dysbiosis of the gut microbiome has been demonstrated in diabetic patients .…”
Section: Discussionmentioning
confidence: 99%
“…A study of supragingival plaque, as well as tongue scrapings and saliva samples used metagenomics and 16S rRNA sequencing for a more comprehensive characterization of the oral microbiome . However, due to ease of sampling, salivary samples provide a distinctive advantage for screening purposes and have been used in various studies of health and disease . In addition to sampling, the choice of hypervariable regions of the 16S rRNA gene that have been sequenced have an impact on characterizing the diversity of the oral microbiome .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…278 Consistent with these findings, it has been found that high levels of salivary glucose (derived from an unbalanced diet) are associated with a reduced bacterial count and modified bacterial frequencies. 279 Fatty acid and vitamin intake can also modify the oral microbiome, with saturated fats being associated positively with a high Betaproteobacteria and Fusobacteria abundance, whereas vitamin C supplementation is associated with the presence of Fusobacteria, Leptotrichiaceae, and Lachnospiraceae; however, these findings involve quite modest relative changes. 278 Oral bacteria can activate alcohol and convert it to the genotoxic and carcinogenic compound, acetaldehyde.…”
Section: Periodontitis and The Microbiomementioning
confidence: 99%